The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/0037-8682-1699-2013
|View full text |Cite
|
Sign up to set email alerts
|

Human adenovirus detection among immunocompetent and immunocompromised patients presenting acute respiratory infection

Abstract: Introduction: Human adenoviruses (HAdV) play an important role in the aetiology of severe acute lower respiratory infection, especially in immunocompromised individuals. The aim of the present study was to detect HAdV using two different methods, direct fluorescence assay (DFA) and nested polymerase chain reaction (nested PCR), in samples collected from patients with acute respiratory infection (ARI) within 7 days of symptom onset. Methods: Samples (n=643) were collected from patients in different risk groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…It has been previously demonstrated that HAdV infections were detected in 8-24.1%, HPIV-3 in 32%, HRSV in 20%, HBoV in 12%, HMPV in 12%, FLUAV in 4%, and FLUBV in 4% of transplant patients. 8,33 HRV and HMPV were detected in 28.6% and 2%, respectively, in elderly patients. 29 Even so, a study performed in Porto Alegre (Southern Brazil) between November 2008 and October 2010 reported that 22% of infections in immunocompetent adult patients (median age 50.6 years of age) admitted to emergence rooms with ILI or severe acute respiratory infection (SARI) were caused by respiratory viruses, mostly FLUAV and HRV-A/B.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been previously demonstrated that HAdV infections were detected in 8-24.1%, HPIV-3 in 32%, HRSV in 20%, HBoV in 12%, HMPV in 12%, FLUAV in 4%, and FLUBV in 4% of transplant patients. 8,33 HRV and HMPV were detected in 28.6% and 2%, respectively, in elderly patients. 29 Even so, a study performed in Porto Alegre (Southern Brazil) between November 2008 and October 2010 reported that 22% of infections in immunocompetent adult patients (median age 50.6 years of age) admitted to emergence rooms with ILI or severe acute respiratory infection (SARI) were caused by respiratory viruses, mostly FLUAV and HRV-A/B.…”
Section: Discussionmentioning
confidence: 96%
“…Acute respiratory infections represent a significant morbidity and mortality burden worldwide and are caused majority of the data collected regarding infections in children and the epidemiology of community-acquired viral respiratory infections among adults is insufficient, perhaps with the exception of infections caused by the influenza virus. Most data available focuses on specific populations such as immunosuppressed, [5][6][7][8][9] homeless, 10,11 or elderly individuals. 5,12,13 Viruses are the leading causes of acute respiratory disease throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in Brazil, few studies involve HAdV detection in ASCT patients [Machado et al, ; Raboni et al, ,; Watanabe et al, ]. None of them have prospectively monitored the patients using feces or serum samples nor performed HAdV molecular characterization.…”
Section: Discussionmentioning
confidence: 99%
“…The hexon protein with serotype specific encoded via seven hyper variable regions (HVR-7) is the essential components for serotype identification of adenoviruses [6,7]. Hence, the molecular methods demonstrate greater sensitivity than conventional assays for detection and identification of adenovirus in respiratory samples by using specific primer for amplifying the HVR-7 of hexon gene which provides easy, quick and accurate detection to all HAdVs serotypes [8,9]. Due to the potential role of HAdVs in the URTIs cases of young children and there is no previous molecular study on these viruses in Iraq, this study aimed to detect of the prevalence of HAdVs in children suffering from URTIs by polymerase chain reaction (PCR).…”
Section: Introductionmentioning
confidence: 99%